PENAMBAHAN SWISS BALL PADA CORE STABILITY EXERCISE DAN CORE STABILITY EXERCISE DAPAT MENINGKATKAN LINGKUP GERAK SENDI DAN AKTIVITAS FUNGSIONAL PADA PETANI WANITA DENGAN LOW BACK PAIN NON SPESIFIK DI KOTA TOMOHON - Novtiyas Maria Pombu; Susy Purnawati; S. Indra Lesmana; Alex Pangkahila; Luh Made Indah Sri Handari Adiputra; Wahyuddin - (Sport and Fitness Journal, 2019)
ABSTRACTBackground: Non-specific low back pains are low back pain caused by disorders or abnormalities in the musculoskeletal element without the presence of neurological disorders that can arise due to potential tissue damage leading to range of motion limitations and decreased functional activity. Objective: To prove that the addition of Swiss ball to core stability exercise and core stability exercise can improve the range of motion and functional activity in female farmers with non-specific low back pain in Tomohon City. Method: This research used true experimental method, with pre-test and post-test group design. This study used 18 subjects divided into 2 groups, Treatment Group I with core stability exercise and Treatment Group II addition of Swiss ball on core stability exercise. Both treatment groups were given training 3 times a week for 4 weeks. The measuring instrument used to measure lumbar LGS is the modified-modified Schober test and lumbar disability is a modified Oswestry disability index. Results: For the result of paired sample t-test of treatment group I LGS flexion and extension obtained p = 0.000 (p <0.05) and treatment group II LGS flexion and extension obtained result p = 0.000 (p <0.05). The decrease of modified ODI value in treatment group I obtained p = 0.000 (p <0.05) and treatment group II was obtained p = 0.000 (<0.05). The independent t-test results showed LGS flexion in treatment group I with p = 0.879 (> 0.05). The value of LGS extension in treatment group I with p value = 0.733 (> 0.05). The result of hypothesis test showed that the decrease of lumbar disability can be evaluated modified ODI in treatment group I with p = 0.891 (> 0.05). Conclusions: There is no statistically different Swiss ball addition to the core stability exercise and core stability exercise in increasing the range of motion and functional activity in female farmers with non-specific low back pain. Keywords: Non-specific low back pain, Swiss ball, core stability exercise, modified-modified Schober test, modified Oswestry disability index.